Effect of Noise Exposure on Occupational Stress and Hypertension among Workers: a Meta-Analysis - Maria Paskanita Widjanarti; Sumardiyono; Aurina Firda Kusuma Wardani (Masters Program in Public Health, 2025)
Background: The work environment greatly affects the health condition of the workers so that there are no work-related accidents or occupational diseases. Noisy physical environmental factors above the threshold value have a risk of causing occupational diseases such as psychological work stress and hypertension. This study aims to analyze the effect of noise exposure on occupational stress and hypertension among workers. Subjects and Method: This study is a systematic review and meta analysis with the following PICO. P: working society, I: exposure noise ≥85 dBA, C: not exposed to noise ≥85 dBA, O: Stress and Hypertension. This study used of articles published between 2009 and 2022 were comprehensively searched for using electronic databases like PubMed, ProQuest, Scopus, and Google Scholar. The keywords to search for articles were “noise exposure” OR “occupational noise” AND “occupational stress” OR “work stress” AND “hypertension”. The adjusted odds ratio was used to evaluate the effect size (aOR). To evaluate the bias risk, the Critical Appraisal Skill Program (CASP) was used. Articles were analyzed using the Review Manager 5.3 application. Results: This study includes 14 papers, using cross-sectional and case-control study designs, from Asia, including Indonesia, Malaysia, China, Jordan, and South Korea. Based on 5 studies cross-sectional on the effects of exposure to noise in the event of work stress, work stress increases 4.88 times compared to workers who are not exposed to noise (aOR=4.88; 95% CI= 1.77 to 13.47; p= 0.002). 9 subgroup studies with cross-sectional and case-control study designs on the effect of noise exposure showed an increase of 2.47 times the incidence of hypertension compared to workers who were not exposed to noise at work (aOR= 2.47; 95% CI= 1.75 to 3.48; p<0.001). Conclusion: Exposure to noise increases the risk of work-related stress and hypertension. Suggestions that can be made are to carry out engineering, periodic measurements, work time management, workforce education and use of PPE.